Regional preferences for hierarchies, markets, and networks: Exploring social capital data for Germany - Lorenz Blume; Detlef Sack (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2006)
Social capital is often defined as consisting of trust and post materialist values on the one hand, and social networks on the other. From an institutionalist point of view this concept is not convincing. Norms (i.e. informal institutions) can combine with different governance modes, not only with networks. The regional governance literature distinguishes between at least three governance modes, hierarchies, markets, and networks, each having its own advantages. This paper examines how regional preferences for these modes are related to trust and post materialist values. A principle component analysis of 48 social capital indicators for 74 West German regions shows that trust and post materialist values do not solely combine with networks but also with preferences for markets and hierarchies. A cluster analysis identifies two dominant types of regional social capital. These types are different from the well-known Italian patterns described by Robert Putnam in his seminal work. In the period 1995- 2002, annual economic growth was on average one percent higher in regions that have combined trust with strong preferences for markets and weak political networks than in opposite regions.
Keywords: 330; Markets; Hierarchies; Networks; Social Capital; Regional Governance